Underwater acoustic localization of marine mammals in an uncertain environment - Rideout, Brendan; Dosso, Stan E.; Hannay, David (Canadian Acoustics, 2009)
An MSc thesis research project aimed at investigating three-dimensional acoustic localization and tracking of vocalizing marine mammals. The main objective of the research project was to provide a more reliable method for assessing temporal variations in walrus population distributions and habitat usage. Investigations revealed that significant changes in the degree of summer ice coverage in the Chukchi Sea along with increased seismic activity in the waters surrounding Alaska had the potential to impact marine mammals, including walruses. The Pacific Walrus was selected for conducting the localization study due to their presence in the investigated area. The study considered two approaches to investigate acoustic localization of the mammals. The first approach used several independent data acquisition systems, while the second approach involved evaluation of a single data acquisition system for three-dimensional acoustic localization.